2022
DOI: 10.1111/his.14843
|View full text |Cite
|
Sign up to set email alerts
|

Primary mucosal melanomas of the head and neck are characterised by overexpression of the DNA mutating enzyme APOBEC3B

Abstract: Aims Primary head/neck mucosal melanomas (MMs) are rare and exhibit aggressive biologic behaviour and elevated mutational loads. The molecular mechanisms responsible for high genomic instability observed in head/neck MMs remain elusive. The DNA cytosine deaminase APOBEC3B (A3B) constitutes a major endogenous source of mutation in human cancer. A3B‐related mutations are identified through C‐to‐T/−G base substitutions in 5′‐TCA/T motifs. Herein, we present immunohistochemical and genomic data suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…IHC clearly shows a strong accumulation of human A3B in the nuclear compartment of cells in multiple murine tissues, consistent with prior reports for human A3B subcellular localization in human cell lines and tissues. [17][18][19][20] These observations demonstrate that higher levels of human A3B are tolerated in primary mouse tissues and, further, that its nuclear import mechanism is conserved, despite the fact that only distantly related polynucleotide deaminase family members are expressed in mice (i.e., Apobec3, Apobec1, and Aicda).…”
Section: Construction Of a Murine Model For Inducible Expression Of H...mentioning
confidence: 84%
“…IHC clearly shows a strong accumulation of human A3B in the nuclear compartment of cells in multiple murine tissues, consistent with prior reports for human A3B subcellular localization in human cell lines and tissues. [17][18][19][20] These observations demonstrate that higher levels of human A3B are tolerated in primary mouse tissues and, further, that its nuclear import mechanism is conserved, despite the fact that only distantly related polynucleotide deaminase family members are expressed in mice (i.e., Apobec3, Apobec1, and Aicda).…”
Section: Construction Of a Murine Model For Inducible Expression Of H...mentioning
confidence: 84%
“…To obtain a global overview of the A3B expression pattern in breast cancer cells, paraffin-embedded sections of an exploratory panel of breast cancer cell lines were subjected to immunohistochemistry (IHC) using a validated antibody against A3B [ 26 , 27 , 28 ]. While this antibody recognizes A3A, A3B, and A3G, detection of A3B is easily distinguished from A3A and A3G during microscopy and immunoblotting due to A3B’s distinct nuclear localization and size, respectively ([ 26 , 27 , 28 ]; discussed in [ 12 ]). We initially chose to investigate MDA-MB-415 and BT474, two cell lines known to express A3B at relatively high levels [ 5 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Detection of A3B by conventional IHC on these cell lines was performed as described in [ 26 , 27 , 28 ]. For multiplex IHC, slides containing cell lines or primary breast cancer specimens were rehydrated by three xylene submersions of 10 min, followed by three 100% ethanol washes, one 70% ethanol wash, one 50% ethanol wash, and a final wash in ddH 2 O. Tissue material was then fixed to the glass slides by a 10-minute incubation in neutral buffered formalin, followed by a wash in ddH 2 O.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic uracil lesions catalyzed by A3B are responsible for a large proportion of both dispersed and clustered mutations in breast, lung, cervix, head, neck and bladder cancers [ 4 6 ]. With defined roles in mutagenesis, A3B is reported to promote both initiation and progression of cancer, and overexpression of A3B is usually associated with poor clinical outcomes of cancer patients [ 7 9 ], including primary head/neck mucosal melanomas (MMs) [ 10 ]. Recently, emerging evidence has demonstrated that A3B activation was positively correlated with elevated levels of DNA RS, pointing to the additional function of A3B in promoting cancer [ 3 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%